Tanggung Jawab Hukum Pejabat Pembuat Akta Tanah (PPAT) atas Pembuatan Akta dalam Sengketa Tanah Warisan Tanpa Hak (Studi Putusan Mahkamah Agung Nomor 2829 K/Pdt/2024) - Mardatillah, Zasmina (JURNAL PENELITIAN SERAMBI HUKUM, 2026)
Inheritance land disputes are one of the most common forms of agrarian conflict in Indonesia. This problem arises when legitimate heirs lose their control rights due to the actions of another party who controls or transfers the inherited land without a valid legal basis. This study examines Supreme Court Decision Number 2829 K/Pdt/2024, which stems from differing considerations between the three levels of justice. The first-instance court rejected the heirs' lawsuit because it was deemed vague and lacking parties, while the High Court partially granted the lawsuit, deeming the heirs to have rights to the disputed land. However, at the cassation level, the Supreme Court again overturned the appeal decision and declared the lawsuit inadmissible. This study uses a normative juridical approach. This study utilizes secondary data consisting of primary legal materials, secondary legal materials, and tertiary legal materials. This study uses qualitative data analysis methods. The research findings indicate that the Supreme Court emphasized the importance of formal legal certainty in the judicial process, thus preventing lawsuits that do not meet formal requirements from being examined further. Consequently, the rights of heirs have not received effective legal protection, even though they are still materially recognized. This decision illustrates the need for a balance between legal certainty and substantive justice to ensure comprehensive protection of the civil rights of heirs.